A new tool for evaluating forages - Harbers, L.H.; Brazle, F.K.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
The scanning electron microscope has been used to observe the digestion of alfalfa hay and warm- and cool-season grasses. Photomicrographs show that leaves of all species are digested by bacteria and protozoa attacking either the upper part of the leaf or exposed edges; lower leaf surfaces are never attacked. Intake of a forage depends on how rapidly rumen bacteria and protozoa can enter the upper leaf surface and digest underlying material (mesophyll) leaving most of the highly lignified nutrient-carrying vessels (vascular tissue) undigested.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Intake; Alfalfa hay; Forage